Long-term activity in and among persons with transfemoral amputation - Halsne, Elizabeth G.; Waddingham, Matthew G.; Hafner, Brian J. (Journal of rehabilitation research and development, 2013)
Although physical limitations associated with transfemoral amputation (TFA) have been studied in laboratory settings, little is known about habitual activity within free-living environments. A retrospective analysis of 12 mo of step activity data was performed to quantify activity levels, variations, and patterns in 17 adults with unilateral TFA. Yearly, seasonal, and monthly average daily step counts and coefficients of variation (CoVs) were examined to characterize mobility. Analysis by Medicare Functional Classification Level (MFCL) was performed to explore relationships between clinical classification and performance. Subjects averaged 1,540 prosthetic steps/day, and activity generally increased with MFCL. Activity between MFCL-2 and -3 subjects was not significantly different, suggesting that ability to engage in habitual physical activity may be similar for these groups. Relative variation (CoV) was 0.65 across subjects but was lower for those with higher activity levels. No significant differences in CoV by group were detected. Marked seasonal and monthly patterns in activity were identified. Warmer seasons and months generally promoted higher activity, but peak temperatures and humidity depressed activity. Results suggest that persons with TFA are greatly limited in regards to activity. Further, large variations within and between subjects may challenge the interpretation of step activity gathered over short periods of time.